2011
DOI: 10.1152/ajplung.00254.2010
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal episodic ozone results in persistent attenuation of pulmonary and peripheral blood responses to LPS challenge

Abstract: Early life is a dynamic period of growth for the lung and immune system. We hypothesized that ambient ozone exposure during postnatal development can affect the innate immune response to other environmental challenges in a persistent fashion. To test this hypothesis, we exposed infant rhesus macaque monkeys to a regimen of 11 ozone cycles between 30 days and 6 mo of age; each cycle consisted of ozone for 5 days (0.5 parts per million at 8 h/day) followed by 9 days of filtered air. Animals were subsequently hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…We do not yet know if age-dependent proinflammatory cytokine synthesis by airway epithelium corresponds to differential respiratory pathogen susceptibility in vivo. However, our previous work has shown that a single LPS aerosol dose administered to juvenile animals results in pulmonary and systemic neutrophilia within 6 hours after exposure, suggesting that innate immune function is sufficient within this age group (31).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We do not yet know if age-dependent proinflammatory cytokine synthesis by airway epithelium corresponds to differential respiratory pathogen susceptibility in vivo. However, our previous work has shown that a single LPS aerosol dose administered to juvenile animals results in pulmonary and systemic neutrophilia within 6 hours after exposure, suggesting that innate immune function is sufficient within this age group (31).…”
Section: Discussionmentioning
confidence: 91%
“…Newborn male rhesus monkeys were housed under high-efficiency particulate air (HEPA) filtered air conditions, as previously described, and evaluated at 1 year of age (31). A subset of animals received a single aerosolized dose of 25,000 EU in PBS via facemask.…”
Section: Animalsmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) were prepared as previously described (17). PBMCs were cultured in 96-well tissue culture plates with AIM-V medium (Invitrogen, Carlsbad, CA) at a concentration of 2 3 10 5 cells/100 ml at 37 8 C in 5% CO 2 .…”
Section: In Vitro Challenge Of Peripheral Blood Cells With Tlr Ligandsmentioning
confidence: 99%
“…Studies in animal models have provided supportive data on immune modulation by air pollution exposure during early life. We have previously reported that peripheral blood cells from juvenile monkeys experimentally exposed to episodic ozone during the first 6 months of life produced significantly reduced levels of proinflammatory cytokines when challenged in vitro with Toll-like receptor (TLR) ligands (17).…”
mentioning
confidence: 99%
“…For example, perinatal environmental tobacco smoke exposure in infant monkeys results in altered immune cytokine profiles and airway innervation [Yu et al, ]. The health effects of environmental exposures can persist long after the exposure has ended, as evidenced in a study by Maniar‐Hew et al [], in which early life ozone exposures resulted in attenuation of innate immune responses in mature monkeys. Nonhuman primate models of allergic airways disease have been in existence for over 40 years, exploiting both a naturally occurring parasitic infection in the wild ( Ascaris spp .)…”
Section: Respiratory Diseasesmentioning
confidence: 99%